A Cohort and Database Study of Airway Management in Patients Undergoing Thyroidectomy for Retrosternal Goitre. Issue 6 (November 2014) - Gilfillan, N.; Ball, C. M.; Myles, P. S.; Serpell, J.; Johnson, W. R.; Paul, E.
Patients undergoing thyroid surgery with retrosternal goitre may raise concerns for the anaesthetist, especially airway management. We reviewed a multicentre prospective thyroid surgery database and extracted data for those patients with retrosternal goitre. Additionally, we reviewed the anaesthetic charts of patients with retrosternal goitre at our institution to identify the anaesthetic induction technique and airway management. Of 4572 patients in the database, 919 (20%) had a retrosternal goitre. Two cases of early postoperative tracheomalacia were reported, one in the retrosternal group. Despite some very large goitres, no patient required tracheostomy or cardiopulmonary bypass and there were no perioperative deaths. In the subset of 133 patients managed at our institution over six years, there were no major adverse anaesthetic outcomes and no patient had a failed airway or tracheomalacia. In the latter cohort, of 32 (24%) patients identified as having a potentially difficult airway, 17 underwent awake fibreoptic tracheal intubation, but two of these were abandoned and converted to intravenous induction and general anaesthesia. Eleven had inhalational induction; two of these were also abandoned and converted to intravenous induction and general anaesthesia. Of those suspected as having a difficult airway, 28 (87.5%) subsequently had direct laryngoscopy where the laryngeal inlet was clearly visible. We found no good evidence that thyroid surgery patients with retrosternal goitre, with or without symptoms and signs of tracheal compression, present the experienced anaesthetist with an airway that cannot be managed using conventional techniques. This does not preclude the need for multidisciplinary discussion and planning.